Recent progress in g–C3N4–Based materials for remarkable photocatalytic sustainable energy. (8th June 2022) - Li, Wei; Sohail, Muhammad; Anwar, Usama; Taha, T.A.; Al-Sehemi, Abdullah G.; Muhammad, Shabbir; Al-Ghamdi, Ahmed A.; Amin, Mohammed A.; Palamanit, Arkom; Ullah, Sami; Hayat, Asif; Ajmal, Zeeshan
Abstract: In recent years, the most appealing way to harvest solar energy via cost-effective, renewable, clean and sustainable technology is the artificial photocatalysis which has drawn multidisciplinary attention to mitigate the upcoming energy disaster and environmental issues in the arena of sustainable development of society. For this purpose, significant progress has been made, regarding the selectivity of photocatalytic energy sources for potential productivity using solar energy pathway, nonetheless it has still become a difficult task for scientists in order to make and resolve the noteworthy problem of increasing global deterioration. According to a recent literature survey, the non-metal based graphitic carbon nitride (g-C3 N4 ) as a fascinating conjugated polymer based photocatalyst has emerged as a new research hotspot in the form of viable option related to its earth abundant elements, good stability, and ease in fabrication. Still, there are many disadvantages associated with g-C3 N4, such as rapid recombination of photoexcited electron-hole pairs, which ultimately affect the photocatalytic hydrogen (H2 ) and carbon dioxide (CO2 ) conversion under solar illumination. Previously published several reviews only emphasize the proficient use of g-C3 N4 photocatalyst for overall sustainable energy production as an effective treatment strategy. But the literature has never been addressed the use of g-C3 N4 with different morphological and structural characteristics for simultaneous H2 production and carbon dioxide reduction. Therefore, the proper designing and development of novel photocatalysts with proper surface tuning and intrinsic properties towards efficient energy harvesting is of utmost interest. This review article is basically designed to properly address the existing issues and the recent progress of g-C3 N4 through various strategies with the aim of obtaining a robust and resourceful photocatalyst towards sustainable energy production. In this context, we had a clear debate regarding the proper tuning of g-C3 N4 based photocatalysts through various fabrication strategies, such as electronic structure via metals/non-metals doping, defects engineering, carbon dots, etc. along with Z-scheme heterojunctions, bimetallic cocatalyst, and organic metal-organic framework. At the end, this review is devoted to sufficiently summarizing the recent advancements and the possible future recommendation of the fundamental contribution of g-C3 N4 in a wide variety of sustainable energy production fields. Graphical abstract: Image 1 Scheme. Proposed graphical illuatration defining the overveiw of this manuscript. Highlights: The photocatalytic main principles of g-C3 N4 were comprehensively evaluated. The key functional characteristics of g-C3 N4 photocatalysts were acknowledged. The various architectural practices for g-C3 N4 photocatalysts were described. The key characteristics of novel g–C3 N4 –based composites were outlined. Significant photocatalytic functionalities of g-C3 N4 were discussed in detail.